A modern econometric approach to estimating theoretically consistent demand systems of retail brands - De Villiers, Dylan (School of Economics, 2014)
This paper conducts an empirical investigation of the cake mix and frosting demand system using daily data on sales figures, prices and marketing mix variables. SUR maximum likelihood is used to estimate static and dynamic (error correction) linear almost ideal demand systems. Results compare static and dynamic model estimates.